Amyloid β chaperone — lipocalin-type prostaglandin D synthase acts as a peroxidase in the presence of heme - Phillips, Margaret (2022)
The extracellular transporter, lipocalin-type prostaglandin D synthase (L-PGDS) binds to heme and heme metabolites with high affinity. It has been reported that L-PGDS protects neuronal cells against apoptosis induced by exposure to hydrogen peroxide. Our study demonstrates that when human WT L-PGDS is in complex with heme, it exhibits a strong peroxidase activity thus behaving as a pseudo-peroxidase. Electron paramagnetic resonance studies confirm that heme in the L-PGDS-heme complex is hexacoordinated with high-spin Fe(III). NMR titration of heme in L-PGDS points to hydrophobic interaction between heme and several residues within the β-barrel cavity of L-PGDS. In addition to the transporter function, L-PGDS is a key amyloid β chaperone in human cerebrospinal fluid. The presence of high levels of bilirubin and its derivatives, implicated in Alzheimer's disease, by binding to L-PGDS may reduce its chaperone activity. Nevertheless, our ThT binding assay establishes that heme and heme metabolites do not significantly alter the neuroprotective chaperone function of L-PGDS. Guided by NMR data we reconstructed the heme L-PGDS complex using extensive molecular dynamics simulations providing a platform for mechanistic interpretation of the catalytic and transporting functions and their modulation by secondary ligands like Aβ peptides and heme metabolites.